Does the Dermatology Life Quality Index (DLQI) underestimate the disease‐specific burden of psoriasis patients?. (27th September 2018) - Langenbruch, A.; Radtke, M.A.; Gutknecht, M.; Augustin, M.
Abstract: Background: The Dermatology Life Quality Index (DLQI) is the most frequently used health‐related quality of life (HRQoL) instrument for skin diseases. According to the DLQI instructions, the responses 'not relevant' and 'my skin problem has not at all affected this aspect of life' ('not at all') have to be scored as 0 = no HRQoL impairments. Objective: The aim of this study was to estimate potential bias of DLQI measurements for patients with psoriasis based on items considered to be not relevant. Methods: One thousand two hundred forty‐three patients with psoriasis were surveyed in a cross‐sectional study. Disease severity (Psoriasis Area and Severity Index, PASI) and subjective health state (EuroQoL Visual Analogue Scale, EQ VAS) were compared per DLQI item between patients who answered the respective question 'not relevant' and those who answered 'not at all'. Results: Patients who declared a DLQI item to be not relevant showed a higher disease severity and a lower health state. Conclusion: Results indicate that patients who declare a DLQI item to be not relevant have a higher disease‐related burden than those who do not feel affected by their psoriasis in the same aspect of life. If aspects of life are considered to be not relevant due to high disease burden, this should be reflected by a HRQoL instrument.